Immunodetection of NETs in Paraffin-Embedded Tissue - Brinkmann, Volker; Abu Abed, Ulrike; Goosmann, Christian; Zychlinsky, Arturo (Frontiers in Immunology, 2016)
The pathogenic potential of NETs was recently described and their detection in tissue could serve as a prognostic marker. NETs are delicate and filigree structures, hence good tissue preservation is essential for their detection. Indeed, analysis of paraffin-embedded tissue has proven superior to the study of cryo sections. Though, under favourable conditions, the presence of NETs can be detected in tissue sections stained with histological dyes, definitive identification of NETs needs the colocalization of immunofluorescent signals for both nuclear and granular (or cytoplasmic) NET components. We tested diverse antigen retrieval methods and various combinations of commercially available antibodies and present here staining protocols to detect NETs in human and murine tissue sections.